Beyond Automated Feedback: An AI-Assisted Pedagogical Framework for Academic Writing in EFL Contexts - Tiara Noviarini; Mark Philip Castillo Paderan; Fini Widya Fransiska; Zohri Hamdani; Musiman Musiman (Universitas Pendidikan Ganesha, 2026)
Academic writing is a fundamental competence for students of English Education programs, yet many EFL students continue to experience persistent difficulties in organizing ideas, maintaining coherence, revising drafts, and applying academic conventions. At the same time, the increasing use of artificial intelligence (AI) tools in writing has raised pedagogical and ethical concerns due to their largely unstructured use. This study aims to develop a pedagogically grounded framework for integrating AI into academic writing instruction in an EFL teacher education context. The study employed a Research and Development approach with a design-based research orientation. Data were collected through a needs analysis questionnaire administered to students, semi-structured interviews with lecturers, and document analysis of academic writing tasks. The proposed framework was evaluated through expert validation and a limited practicality test involving lecturers and students. The results of the needs analysis indicate that students require structured guidance across all stages of the writing process, particularly in revision and formative feedback. Expert validation results demonstrate that the developed framework is pedagogically feasible, conceptually clear, and contextually relevant to EFL academic writing instruction. In addition, the practicality test shows that the framework is perceived as applicable and supportive of both student autonomy and lecturer guidance. This study does not measure learning effectiveness but provides a validated pedagogical design for responsible AI integration. It is recommended that lecturers adopt structured AI-guided writing frameworks to support formative feedback and that future research examine the effectiveness of the framework through experimental or longitudinal studies.